2020
DOI: 10.1021/acschemneuro.0c00315
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Improvement by Vorinostat through Modulation of Endoplasmic Reticulum Stress in a Corticosterone-Induced Chronic Stress Model in Mice

Abstract: Chronic stress is the leading cause of memory impairment today. Various stress-based models are being developed for studying cognitive impairment. Repurposing of existing drugs in a new pharmacology class is the safest and cheapest option for treatment instead of new drug discovery. Vorinostat (VOR) is the first histone deacetylase (HDAC) inhibitor approved for the treatment of cutaneous T-cell lymphoma by the U.S. FDA. VOR follows the rule of five and is reported to cross the blood−brain barrier. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In addition to the antidepressant effect, HDAC inhibitors promoted neuronal rewiring and recovery of motor functions after traumatic brain injury [143]. Also, HDAC inhibitors such as sodium butyrate and SAHA enhanced cognitive function, which may provide therapeutic options for depression that accompanies cognitive impairment [144][145][146]. A recent drug repositioning study for precise/personalized medicine in depression using bioinformatic analyses revealed that HDAC inhibitors such as trichostatin A and valproic acid as a new potential antidepressant drug [117].…”
Section: Molecular Therapeutics Of Depression: An Epigenetic Perspectivementioning
confidence: 99%
“…In addition to the antidepressant effect, HDAC inhibitors promoted neuronal rewiring and recovery of motor functions after traumatic brain injury [143]. Also, HDAC inhibitors such as sodium butyrate and SAHA enhanced cognitive function, which may provide therapeutic options for depression that accompanies cognitive impairment [144][145][146]. A recent drug repositioning study for precise/personalized medicine in depression using bioinformatic analyses revealed that HDAC inhibitors such as trichostatin A and valproic acid as a new potential antidepressant drug [117].…”
Section: Molecular Therapeutics Of Depression: An Epigenetic Perspectivementioning
confidence: 99%
“…HDACis, such as sodium butyrate and SAHA, promote cognitive function, and may provide therapeutic options for depressed patients with cognitive impairment. 405 407 Although medications targeting these epigenetic molecules are proving effective in preclinical animal studies, there is a lack of successful clinical trials of HDACi in neuropsychiatric disorders, perhaps because of the complexity of different HDAC isoforms (i.e., HDAC2 and HDAC5) that are associated with pro-depressant and antidepressant functions. 408 The complexity is further heightened because HDAC and DNMT are widely distributed in the CNS and peripheral tissues.…”
Section: A Translational Perspective On Epigenetic Modifications In Mddmentioning
confidence: 99%
“…Recent work reported in ACS Chemical Neuroscience has demonstrated cognitive improvement stimulated by the HDAC inhibitor vorinostat, in a mouse model of chronic stress. 14 Powerful PET imaging tools that enable visualization of HDAC6 occupancy in vivo have also been reported recently. 15 Since our previous special issue, molecular investigations focusing on disease-related epigenetic processes in non-human species, including disease-causing parasites, are starting to emerge.…”
mentioning
confidence: 99%